2015
DOI: 10.1080/15287394.2014.960045
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological Assessment of Tannery Effluent Using Guppy Fish (Poecilia reticulata) as an Experimental Model: A Biomarker Study

Abstract: Tannery wastewater in the East Calcutta Wetlands (a Ramsar site of West Bengal; number 1208) exerts adverse effects on commercial fish production and subsequently affects humans. The present study was conducted to investigate acute and chronic toxicity of tannery effluent on a fish biosystem by examining oxidative stress enzyme expression in different organs including liver, gills, and muscle following exposure. Phosphatases, both alkaline phosphatase and acid phosphatase, and antioxidant superoxide dismutase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…When considering biomarkers of pollution in fish species, liver and gills are the most utilized tissues reported in literature, even though recent studies have been using muscle and brain tissues in biomarker analysis (Ghazala et al 2014;Aich et al 2015). Here, we have shown that both fish species studied showed visible alterations in stress-related biomarkers in muscle and brain.…”
Section: Stress Markers In Zebrafishmentioning
confidence: 63%
“…When considering biomarkers of pollution in fish species, liver and gills are the most utilized tissues reported in literature, even though recent studies have been using muscle and brain tissues in biomarker analysis (Ghazala et al 2014;Aich et al 2015). Here, we have shown that both fish species studied showed visible alterations in stress-related biomarkers in muscle and brain.…”
Section: Stress Markers In Zebrafishmentioning
confidence: 63%
“…Some of the toxins decay or volatilize to form insoluble salts and rest are precipitated and get combined into the substrate in bed surface. Fish species are the perfect model for sensing the occurrence of genotoxic toxins in aquatic ecosystems (Aich et al, 2015;Walia et al, 2015; because these aquatic organisms are very sensitive to little quantity of metals within the water body, are abundant, and also live in some different habitats (Ali et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Poecilia reticulata is a relevant experimental fish model (Ferreira et al, 2012;Aich et al, 2015) and mosquito's natural enemy. However the findings that spinosad exerted direct effects on P. reticulata suggests that the larvivorous potential of this fish species may be diminished based upon the adverse behavioral responses noted.…”
Section: Resultsmentioning
confidence: 99%